The Use of Metacognitive Reading Strategies by EFL Learners in Reading - Tika Suharni (Research in English and Education Journal, 2017)
Reading is considered as one of the most important skills in learning English as a foreign Language. Furthermore, it is important for the students to comprehend the text that they read and aware of the strategies they use in the reading process. Nevertheless, the students may have to deal with the problems when they read in English especially an academic text. In this case, it is necessary to find out about the students’ awareness and discover the use of reading strategies in reading process. This study aimed to reveal the students metacognitive awareness and the metacognitive reading strategies that are frequently used. In this study, quantitative research method was used through the implementation of Survey of Reading Strategies (SORS) questionnaire by Mokhtari and Reichard (2002).  The questionnaires were distributed to thirty students of a Critical Reading Class in Study Program of English Education, Syiah Kuala University. The results indicated that the students have high awareness of metacognitive reading strategies and use Problem Solving Reading Strategies (PROB) with high frequency.